Identification of common hub genes and construction of immune regulatory networks in aplastic anemia, myelodysplastic syndromes, and acute myeloid leukemia - Shan, Mingliang; Xu, Li; Yang, Wenzhe; Sui, Lili; Sun, Ping; Zhuo, Xiumei; Liu, Shiguo (Frontiers in Immunology, 2025)
BackgroundAplastic anemia (AA), myelodysplastic syndromes (MDS), and acute myeloid leukemia (AML) exhibit complex pathogenic mechanisms and interrelated characteristics. We aimed to identify the common hub genes, establishing a foundation for preventing disease progression.MethodsWe selected relevant datasets from the Gene Expression Omnibus(GEO) database for differential gene expression, gene set enrichment, and weighted gene co-expression network analyses to identify hub genes, and then validated them. Subsequent analyses included immune infiltration analysis, single-cell sequencing, and cell communication analysis. We performed Mendelian randomization to screen inflammatory factors and immune cells. We used RT-qPCR, Enzyme - Linked Immunosorbent Assay(ELISA), and cell proliferation assays to validate the identified hub genes, their relationship with cellular communication mediators and inflammatory factors, and their impact on cellular function.ResultsPOLG and MAP2K7 were identified as common hub genes, with low expression observed across AA, MDS, and AML. There were distinct immune differentials among these diseases, with an enhanced correlation between immune cells and hub genes as the disease progressed. Macrophage Migration Inhibitory Factor(MIF) emerged as a key mediator of cellular communication. We identified 20 regulatory pathways of immune cells and inflammatory factors across different disease stages. In vitro validation confirmed low expression of the hub genes, which were inversely correlated with MIF and inflammatory factors, though they showed no significant impact on cell proliferation or migration.ConclusionsPOLG and MAP2K7 demonstrate crucial roles in the progression from AA to MDS and, ultimately, to AML. These genes regulate more than 20 immune regulatory pathways through MIF-mediated communication, thereby influencing disease progression.